Moore and Wittgenstein on Certainty. - Stroll, Avrum (Oxford University Press, 1994)
The philosophical relationship between Wittgenstein and G.E. Moore and their overlapping, but nevertheless differing, views are the subject of this book. It provides a critical analysis of their differing approaches to a set of fundamental epistemological problems.